2019
DOI: 10.1038/s41598-019-52893-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-induced neuroinflammation is associated with disrupted colonic and bacterial homeostasis in female mice

Abstract: Chemotherapy treatment negatively affects the nervous and immune systems and alters gastrointestinal function and microbial composition. Outside of the cancer field, alterations in commensal bacteria and immune function have been implicated in behavioral deficits; however, the extent to which intestinal changes are related to chemotherapy-associated behavioral comorbidities is not yet known. Thus, this study identified concurrent changes in behavior, central and peripheral immune activation, colon histology, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 83 publications
6
64
0
Order By: Relevance
“…Increases gut permeability, as indicated by 5-fold elevation in circulating LPS-binding protein and systemic inflammation [ 69 ]…”
Section: Effects Of Intestinal Microbiota On Cancer Therapymentioning
confidence: 99%
“…Increases gut permeability, as indicated by 5-fold elevation in circulating LPS-binding protein and systemic inflammation [ 69 ]…”
Section: Effects Of Intestinal Microbiota On Cancer Therapymentioning
confidence: 99%
“…Emerging evidences have shown that the tumor microenvironment (TME) would foist a series of biological barriers to retard effective cancer treatment [1][2][3][4][5]. As a mainstream cancer treatment modality in the clinic, chemotherapy is far from satisfactory due to its limited therapeutic efficacy and severe side effects [6][7][8][9]. To achieve effective cancer chemotherapy with high safety, various nanoscale drug delivery systems enabling tumor-targeted delivery of chemotherapeutics have been intensively explored in the past decades [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a high demand of the drugs for new therapies to treat or prevent this life threatening disease is the need of the time 11 . Natural drugs are more preferred in the cancer treatment as chemoand radiation therapy have several ill effects on human beings 12 . Plant based metabolites have been studied extensively for their anticancer properties 13 .…”
mentioning
confidence: 99%